Advanced oxidation processes for water and wastewater treatment - Parsons, Simon, ....- (London : IWA, 2004)
Samenvatting:The suitability of Advanced Oxidation Processes (AOPs) for pollutantdegradation was recognised in the early 1970s and much research anddevelopment work has been undertaken to commercialise some of theseprocesses.AOPs have shown great potential in treating pollutants at both low andhigh concentrations and have found applications as diverse as groundwater treatment, municipal wastewater sludge destruction and VOCscontrol.Advanced Oxidation Processes for Water and Wastewater Treatment is anoverview of the advanced oxidation processes currently used or proposedfor the remediation of water, wastewater, odours and sludge.The book contains two opening chapters which present introductions toadvanced oxidation processes and a background to UV photolysis, sevenchapters focusing on individual advanced oxidation processes and,finally, three chapters concentrating on selected applications ofadvanced oxidation processes.Advanced Oxidation Processes for Water and Wastewater Treatment will beinvaluable to readers interested in water and wastewater treatmentprocesses, including professionals and suppliers, as well as students andacademics studying in this area.Dr Simon Parsons is a Senior Lecturer in Water Sciences at CranfieldUniversity with ten years' experience of industrial and academic researchand development.
Keywords: Afvalwaterzuivering